Invasive Mold Infections (IMIs) of the Central Nervous System (CNS) in Patients with Hematologic Cancer (HC) (2000–2016): Uncommon but Deadly. (4th October 2017) - Economides, Minas Platon; Ballester, Leomar; Kumar, VInc.e; Jiang, Ying; Tarrand, Jeffrey J; Prieto, Victor; Torres, Harrys; Kontoyiannis, Dimitrios P
Abstract: Background: There is paucity of data regarding IMIs of the CNS in patients with HC or stem cell transplantation (SCT). Methods: Review of the records of patients with HC and/or SCT recipients who were diagnosed with CNS IMIs at MD Anderson Cancer Center (1/1/2000–5/31/2016). IMIs were classified as proven or probable (EORTC/MSG criteria). We excluded patients with mixed CNS infections. Risk factors for survival at day 42 post diagnosis (dx) were assessed. A multivariate logistic regression analysis was performed to identify independent predictors of mortality. Results: We identified 40 patients (16 proven; 40%). Most patients were white (29; 73%) and male (33; 83%). Median age was 58 years. The most common HC was acute leukemia (23; 58%). Seventeen patients (43%) were SCT recipients; 13 (76%) had GVHD. Most patients had active HC and neutropenia at dx (38; 95% and 21; 53%, respectively). Twenty-seven patients (68%) were in the ICU at dx. Aspergillus sp. (13; 33%) and Mucorales (8; 20%) accounted for >50% of cases. CNS IMIs were deemed to be secondary to direct extension or hematogenous spread in 9 (23%) and 31 (77%) patients, respectively. In the latter group, 28/31 (90%) had fungal pneumonia. Of the 27 and 9 patients who had Aspergillus galactomannan antigen tested from serum and CSF, respectively, 18 had positivity in serum (66%) and 3 in CSF (33%). Most patients (30; 75%) had exposure to mold-active agents within 30d of dx. Most patients (34; 85%) received lipid AMB and were treated with combination therapy (33; 83%). Most CNS lesions presented as ring-enhancing abscesses radiographically (26; 65%). Absence of giant cells and granulomas in the pathologic examination of the brain lesions were associated with increased 42 days mortality (0% vs. 70%, P = 0.01 and 0% vs. 60% in those who survived, P = 0.03, respectively). In multivariate analysis, co-infection at the time of dx was associated with increased mortality (OR: 16.5, 95% CI: 1.4–198.3, P = 0.03) while steroid tapering was associated with decreased mortality (OR: 0.06, 95% CI: 0.01–0.53, P = 0.01). There was a trend towards protective role of surgical drainage (OR n = 0.18, 95% CI = 0.03–1.14, P =  0.07). Conclusion: CNS IMIs occur in ill patients with active HC who are often pre-exposed to antifungals. Immune response in pathology, steroid tapering and possibly surgical drainage are associated with improved outcome. Disclosures: D. P. Kontoyiannis, Pfizer: Research Contractor, Research support and Speaker honorarium. Astellas: Research Contractor, Research support and Speaker honorarium. Merck: Honorarium, Speaker honorarium. Cidara: Honorarium, Speaker honorarium. Amplyx: Honorarium, Speaker honorarium. F2G: Honorarium, Speaker honorarium